Analisis Keanekaragaman Jenis Burung Air di Divisi I dan Divisi II PT. Gunung Madu Plantations Kabupaten Lampung Tengah Provinsi Lampung - Hidayat, Apri; Dewi, Bainah Sari (Jurnal Sylva Lestari, 2017)
Gunung Madu Plantations (GMP) Inc. contained high biodiversity, one of that is water birds in its plantation. Division I and Division II are known as the places where diverse water birds inhabited. Gunung Madu Plantation Inc. It self didn't have database of water birds biodiversity yet. According to these, the research need to be done to analyze water birds biodiversity in Division I and Division II of GMP Inc. The research was conducted in October-November 2015, which used of point count method. The study showed about 10 species were found with total individual about 3420 individual, which included within 4 families; Ardeidae, Alcedinidae, Anatidae and Rallidae. The biodiversity index about (H'=2,137), which categorized as mediocre level, in stable condition and eveness point about (J=0,928). Keywords: biodiversity, water birds, point count